Violência escolar no município de Apucarana : uma análise a partir das escolas públicas estaduais - Silva, Douglas Pereira da (2016)
The objective of this study is to specify the functions of the community school patrol in the school environment. The confection of work is justified by the existence of a conflict situation about what is the true role of the police in the school environment. The main question of the study was to try to understand what role the police, at school, in the philosophy community policing. The fundamental hypothesis is founded on the fact that the events that occur in the school environment, especially in the relationship between people (teacher-student, studentstudent, student-employee, etc.) are those classified by researchers as micro violences or incivilities (Abramovay et. al., 2009). The survey contain qualitative and quantitative methods. the quantitative method was founded in the examination of the bulletins of unified occurrences (BOU), issued by the school patrol in the period. Then, the numerical data analysis was performed using statistical procedures. Finally, there was a qualitative analysis of police reports, in which the members of the school community were victims of certain police reports, such as bodily injury, insult, threats, blows, injury. With the help of social science theory, sought to identify if, in this case, the event was from the police jurisdiction or could be solved in other ways. With the results, was identified a set of recommendations for the community school patrol action. To reach these Recommendations used the following method: was identified the main problem that occurs in schools; Was identified its characteristics, and their possible causes and finally was elaborated a set of recommendations, focusing on the work of the community school patrol.